Sentiment Analysis Classification of ChatGPT on Twitter Big Data in Indonesia Using Fast R-CNN - Sio Jurnalis Pipin; Frans Mikael Sinaga; Sunaryo Winardi; Muhammad Noor Hakim (Universitas Budi Darma, 2023)
The advent of OpenAI's ChatGPT, a large language model (LLM) proficient in various fields including artificial intelligence (AI) and natural language processing (NLP), has ignited a plethora of opinions and discussions, especially on social media platforms like Twitter in Indonesia. This research seeks to delve into the intricate dynamics of these discussions, aiming to map both the commendations and criticisms surrounding ChatGPT's technological advancements and potential negative impacts. Utilizing deep learning-based sentiment analysis techniques, the study employs Convolutional Neural Network (CNN) and Fast Region-based Convolutional Network (Fast R-CNN) to analyze a dataset consisting of 7,604 tweets categorized into